Preemergence Herbicides for Use in Ornamentals - Robert H. Stamps; Diane K. Rock; Jeffrey G. Norcini (EDIS)
This is document OH-94, one of a series of the Department of Environmental Horticulture, UF/IFAS Extension. First published March 1993. Revised November 2005.